2023
DOI: 10.1021/jacs.3c03128
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Growth of One-Dimensional Carbides in Single-Walled Carbon Nanotubes with Strong Interaction for Catalysis

Abstract: Tungsten and molybdenum carbides have shown great potential in catalysis and superconductivity. However, the synthesis of ultrathin W/Mo carbides with a controlled dimension and unique structure is still difficult. Here, inspired by the host−guest assembly strategy with single-walled carbon nanotubes (SWCNTs) as a transparent template, we reported the synthesis of ultrathin (0.8−2.0 nm) W 2 C and Mo 2 C nanowires confined in SWCNTs deriving from the encapsulated W/Mo polyoxometalate clusters. The atom-resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…[ 28,29 ] Chemically and thermally robust CNTs and BNNTs promote the coaxial growth of various 1D materials inside or outside to form 1D vdW heterostructures. [ 30–42 ] In particular, insulating BNNTs, whose bandgap is ≈6 eV regardless of their morphology, can serve as “nano‐test‐tubes” that exhibit negligible interference with the intrinsic electronic properties of guest materials. [ 43–45 ] To date, CNTs and BNNTs have been used as templates to stabilize SW‐MoS 2 NTs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28,29 ] Chemically and thermally robust CNTs and BNNTs promote the coaxial growth of various 1D materials inside or outside to form 1D vdW heterostructures. [ 30–42 ] In particular, insulating BNNTs, whose bandgap is ≈6 eV regardless of their morphology, can serve as “nano‐test‐tubes” that exhibit negligible interference with the intrinsic electronic properties of guest materials. [ 43–45 ] To date, CNTs and BNNTs have been used as templates to stabilize SW‐MoS 2 NTs.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated the well-encapsulation of various types of guests into SWCNTs, including small molecules, carbon chains, clusters, and quasi-1D nanomaterials due to their spatial restriction of the channels and host–guest electronic interaction. Such well-defined SWCNT/guest hybrids often exhibited fascinating physical and chemical properties, such as tunable magnetic property, ultrafast proton transport, phase transition, enhanced catalysis, ,, and electrochemical activities, , which originated from modulated electronic properties of SWCNTs. Moreover, SWCNTs can also act as a templated nanoreactor to unveil the dynamic evolution , and transport behavior , of guests inside.…”
Section: Introductionmentioning
confidence: 99%
“…2 An increasing number of studies have demonstrated the well-encapsulation of various types of guests into SWCNTs, including small molecules, 3 carbon chains, 4 clusters, 5−10 and quasi-1D nanomaterials 11−20 due to their spatial restriction of the channels and host−guest electronic interaction. Such well-defined SWCNT/guest hybrids often exhibited fascinating physical and chemical properties, such as tunable magnetic property, 21 ultrafast proton transport, 22 phase transition, 23 enhanced catalysis, 18,24,25 and electrochemical activities, 22,26−30 which originated from modulated electronic properties of SWCNTs. Moreover, SWCNTs can also act as a templated nanoreactor to unveil the dynamic evolution 17,31−33 and transport behavior 34,35 of guests inside.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The coating method, which means attachment to the outer surface of a 1D material by vdW interaction, has been successfully used to obtain BN and MoS 2 nanotubes on the surface of single-walled carbon nanotubes (SWCNTs). However, it should be pointed out that, due to the strong strain effect caused by the curved surface, the growth efficiency and the diameter of the grown nanotube have been greatly limited. , Meanwhile, a variety of 1D vdWHs have been prepared by filling materials into the 1D cavity of nanotubes, including molecules, elements, halides, chalcogenides, transition metal carbides, and perovskites. , However, the low synthesis efficiency of 1D vdWHs materials and the fact that carbon nanotubes contain both semiconducting and metallic types , increase the difficulty of electrical study in 1D vdWHs. There has been little research on the electrical behavior and interlayer interaction of 1D vdWHs.…”
mentioning
confidence: 99%
“…And the G band, which corresponds to transverse and longitudinal plane phonons, shifts from 1588 to 1596 cm –1 (Figure c). Since both the blue shift in the RBM and G band have been considered as a sign of electrons donated by SWCNT, ,, it is concluded that there is interlayer charge transfer from SWCNT to AgI, which affects the valence band electron configuration of SWCNT. The blue shifts of the 2D bands also verify the transfer of electrons in AgI@SWCNT vdWHs (Figure S4).…”
mentioning
confidence: 99%